2003
DOI: 10.1079/pns2003277
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling protein 3 and physical activity: the role of uncoupling protein 3 in energy metabolism revisited

Abstract: Physical activity influences energy metabolism in human subjects by increasing activity-induced energy expenditure and resting metabolic rate for several hours after exercise. On the other hand, physical activity increases mechanical energy efficiency, suggesting that trained subjects would need less energy for daily activities. The underlying mechanism by which physical activity influences energy metabolism is largely unknown. The skeletal muscle-specific homologue of uncoupling protein (UCP) 1, UCP3, could p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 72 publications
4
44
1
Order By: Relevance
“…Overall, gene expression of UCP2 and 3 is affected by situations characterized by changes in energy expenditure and substrate oxidation. [12][13][14][15] UCP2 expression in liver was doses dependently increased by EGCG and doubled in the 1% group. In skeletal muscle, however, UCP2 expression was not increased, on the contrary, it was rather decreased, although not reaching statistical significance due to high interindividual variability.…”
Section: Egcg Prevents Obesity S Klaus Et Almentioning
confidence: 90%
See 1 more Smart Citation
“…Overall, gene expression of UCP2 and 3 is affected by situations characterized by changes in energy expenditure and substrate oxidation. [12][13][14][15] UCP2 expression in liver was doses dependently increased by EGCG and doubled in the 1% group. In skeletal muscle, however, UCP2 expression was not increased, on the contrary, it was rather decreased, although not reaching statistical significance due to high interindividual variability.…”
Section: Egcg Prevents Obesity S Klaus Et Almentioning
confidence: 90%
“…We evaluated the acute effects of orally administered TEAVIGOt on body temperature, energy expenditure, and substrate oxidation, and also the long-term effects of dietary supplementation on development of dietinduced obesity in mice. Since uncoupling proteins (UCPs) are considered to be implicated in thermogenesis and energy metabolism, [12][13][14][15] we investigated the effect of dietary EGCG supplementation on UCP1-3 gene expression in various organs. Furthermore, we analysed expression of key genes in lipid and glucose metabolism in liver and adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
“…1 Based on its closed sequence homology with uncoupling protein-1 (UCP1), a protein that uncouples respiration from ATP production in brown adipose tissue thereby promoting heat production in response to cold or overfeeding, it has been suggested that UCP3 could be involved in the control of muscle energy expenditure. 2 Although the molecular basis of this mechanism is unclear, UCP3 could be considered as a potential therapeutic target of obesity considering its involvement in metabolic efficiency. To date, there is no consensus regarding the exact function of UCP3.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]. One such hypothesis supposes that UCP3 mediates the transport of fatty acid anions from the mitochondrial matrix (4,5), allowing high fatty acid oxidation rates (4) or protecting against lipotoxicity (5). However, using complementary mechanistic approaches on mitochondria from wild-type and UCP3-null mice, Seifert et al (6) excluded a role for UCP3 in catalyzing the export of fatty acid anions from the matrix.…”
mentioning
confidence: 99%